Effect of Gonadotrophin Releasing Hormone (GnRH) on ovulation in Buffaloes Superovulated with pregnant mare serum gonadotrophin - SODHI, H S; SINGH, MEHAR; MATHAROO, J S (The Indian Journal of Animal Reproduction, 2023)
Four healthy normally cycling buffaloes were selected and superovulated with 2500 IU PMSG each. Half of the donors (Group A) were given 0. 1 mg GnRH (Vet Veb Berlin Chemie) on day O at the time of artificial insemination. Superovulation response was assessed on day 7 by rectal palpation of ovaries. On an average there were 4.0±0.0, 4.0± 1.0 Corpora lutea and 1.0± 1.0, 1.0, 4.0±4.0 unovulatory follicles (UF) for group A and B, respectively. Ovulation rate was 80 per cent ( 4 / 5) for group A and 50 per cent (4/8) for group B.